Jiyuan Oridonin A Overcomes Differentiation Blockade in Acute Myeloid Leukemia Cells With MLL Rearrangements via Multiple Signaling Pathways - Qu, Mei; Duan, Yu; Zhao, Min; Wang, Zhanju; Zhao, Mengjie; Zhao, Yao; Wang, Haihua; Ke, Yu; Liu, Ying; Liu, Hong-Min; Wei, Liuya; Hu, Zhenbo (Frontiers in Oncology, 2021)
Differentiation therapy with all-trans-retinoic acid (ATRA) in acute promyelocytic leukemia (APL), a subtype of acute myeloid leukemia (AML), has been extremely successful in inducing clinical remission in APL patients. However, the differentiation therapy of ATRA-based treatment has not been effective in other subtypes of AML. In this study, we evaluated a small molecule of ent-kaurene diterpenoid, Jiyuan oridonin A (JOA), on the differentiation blockade in AML cells with the mixed lineage leukemia (MLL) gene rearrangements (MLLr) in MV4-11, MOLM-13 and THP-1 cells. We found that JOA could significantly inhibit the proliferation of MOLM-13, MV4-11 and THP-1 cells. Moreover, JOA promoted cell differentiation coupled with cell-cycle exit at G0/G1 and inhibited the colony- forming capacity of these cells. We showed that the anti-proliferative effect of JOA attributed to cell differentiation is most likely through the martens tretinoin response up pathway in the MOLM-13 cell line, and the hematopoietic cell lineage pathway by the inhibition of c-KIT expression and cell adhesion pathway in the THP-1 cell line. Our findings suggest that JOA could be a novel therapeutic agent against human MLLr acute myeloid leukemia.